Numerical simulation analysis of mine pressure distribution of shallow coal seam by truncated short wall beam theory - An Bo; Zheng Xiaohui; Zhu Chun; Zhao Junzheng; Tao Zhigang; He Manchao (矿业科学学报, 2019)
Based on the theory of “cutting short-wall beam”,the automatic cutting-in coal-free pillar mining technology for roof-cutting pressure relief is widely used in engineering practice.However,due to the limitation of the numerical modeling of large deformation materials,the numerical simulation analysis of mine pressure distribution based on theory of truncated short wall beam has not been studied.In this paper,the numerical simulation model of NPR bolt/cable is established at the first based on the constant resistance mechanical mechanism of the NPR bolt/cable in the supporting process,achieving the goal of numerical and programmed calculation of large deformation materials .Then,based on the background of Hecaogou No.2 coal mine engineering,mine pressure in longwall mining is continuously monitored on-site.Finally,the numerical simulations and comparative analysis of mine pressure distribution by applying theory of truncated short wall beam on 1105 working face were made through FLAC3D program.The paper reveals the different characteristics of the distribution of abutment pressure under traditional technology and the working face of theory of truncated short wall beam,and this lays a theoretical foundation for the study of stress field distribution and the rule of temporal and spatial variation of rock mass structure using theory of truncated short wall beam.